PENGARUH WAKTU INOKULASI Trichoderma sp. DAN FUNGI MIKORIZA ARBUSKULA (FMA) TERHADAP PERTUMBUHAN BIBIT MANGGIS (Garcinia Mangostana L.) - Jamin, Muhamad; Wulandari, Reine Suci; Suryantini, Rosa (Universitas Tanjungpura, 2017)
Mangosteen is an annual plant whose vegetative growth such as roots, stems and leaves runs very slowly. To spur the growth of mangosteen used biological agents Trichoderma sp. and Arbuscular Mycorrhizal Fungi. The combination of Trichoderma sp. and FMA can accelerate plant growth, root development, and increase nutrients, but not yet known when the inoculation of Trichoderma sp. which is effective on morphorous soils that can increase the growth of mangosteen plants. This study aims to obtain the infuence of inoculation time Trichoderma sp. and Arbuscular Mycorrhizal Fungi (FMA) are effective in improving the growth of mangosteen seeds. This study was designed in RIL (Completely Randomized Design) with the treatment : without Trichoderma and FMA (W0), FMA inoculation without Trichoderma (W2), Trichoderma inoculation together with FMA (W3), Trichoderma inoculation 3 days after inoculation of FMA (W4), and Trichoderma inoculation 7 days after inoculation of FMA (W5). Each treatment was repeated five times so that there were 30 experimental units. The observed variables were height (cm) and plant diameter (mm), number of leaf buds, and FMA colonization at root (%). Maintenance conducted is watering and weeding. The results showed that the parameters of treatment time of inoculation Trichoderma sp. and Arbuscular Mycorrhizal Fungi have no significant effect on the growth of height, diameter and number of leaf buds. This is because the research time is relatively short. Therefore, the need for further research with a longer period of time.Keyword: Arbuscular Mycorrhizal Fungi (FMA), Diameter, Garcinia mangostana L, High, Leaf bud, Trichoderma sp.